On the taxonomy of the genus Hymenicoides Kemp, 1917 (Crustacea: Decapoda: Brachyura: Hymenosomatidae), with resurrection of Limnopilos Chuang & Ng, 1991, and descriptions of two new species - Naruse, Tohru; Ng, Peter K.l. (Zootaxa, 2007)
The systematics of the false spider crab genus Hymenicoides Kemp, 1917 (Hymenosomatidae), is revised. Hymenicoides carteri, type species of the genus, has a distinct locking structure of male abdomen as well as possession of a strong tubercle on the palm of the chela, features which are quite different from H. naiyanetri (Chuang & Ng, 1991), and H. microrhynchus Ng, 1995. The present study restricts Hymenicoides Kemp, 1917, for H. carteri and resurrects Limnopilos Chuang & Ng, 1991, for the other two species. Two new species, one of Hymenicoides from Myanmar, and one of Limnopilos from Sumatra, are also described. A key to the species of both genera is provided.